2021
DOI: 10.1186/s12936-021-03585-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial efficacy and resistance monitoring of artemether-lumefantrine and dihydroartemisinin-piperaquine shows inadequate efficacy in children in Burkina Faso, 2017–2018

Abstract: Background The World Health Organization recommends regularly assessing the efficacy of artemisinin-based combination therapy (ACT), which is a critical tool in the fight against malaria. This study evaluated the efficacy of two artemisinin-based combinations recommended to treat uncomplicated Plasmodium falciparum malaria in Burkina Faso in three sites: Niangoloko, Nanoro, and Gourcy. Methods This was a two-arm randomized control trial of the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 26 publications
1
54
2
Order By: Relevance
“…However, when accounting for a 95% confidence interval, the 86.0–95.9% PCR-corrected efficacy range of AL indicates that continued frequent efficacy monitoring of this drug is warranted in Mali. These findings are not unlike those from Uganda [ 35 ], Angola [ 36 ], and Burkina Faso [ 37 ], which have also shown AL not performing as well as other artemisinin-based combinations, such as ASAQ and DP. Similar to the AL day 28 uncorrected efficacy of 83.4% in this study, two other studies from Mali examining day 28 uncorrected efficacy reported results of 83.8% and 84.5% [ 33 , 34 ] and the study performed in Burkina Faso by Tinto & al, gave 58.4% for ASAQ and 46.1% for AL [ 32 ].…”
Section: Discussioncontrasting
confidence: 70%
“…However, when accounting for a 95% confidence interval, the 86.0–95.9% PCR-corrected efficacy range of AL indicates that continued frequent efficacy monitoring of this drug is warranted in Mali. These findings are not unlike those from Uganda [ 35 ], Angola [ 36 ], and Burkina Faso [ 37 ], which have also shown AL not performing as well as other artemisinin-based combinations, such as ASAQ and DP. Similar to the AL day 28 uncorrected efficacy of 83.4% in this study, two other studies from Mali examining day 28 uncorrected efficacy reported results of 83.8% and 84.5% [ 33 , 34 ] and the study performed in Burkina Faso by Tinto & al, gave 58.4% for ASAQ and 46.1% for AL [ 32 ].…”
Section: Discussioncontrasting
confidence: 70%
“…A target dose (range) of 4 (2-10) mg/kg bw per day dihydroartemisinin and 18 (16-27) mg/kg bw per day piperaquine given once a day for 3 days for children weighing ≥ 25 kg. The target doses and ranges for children weighing < 25 kg are 4 (2.5-10) mg/kg bw per day dihydroartemisinin and 24 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) mg/kg bw per day piperaquine once a day for 3 days.…”
Section: Interventionsmentioning
confidence: 99%
“…There are a few reports on artemisinin resistance mediated by mutations kelch13 (K13) gene in Greater Mekong Sub-region [19], Sudan [20], higher prevalence (42%) in Myanmar [21], and low frequency of kelch13 (K13) gene mutation in 18 Sub-Saharan African countries [22,23]. In addition, over the past ten years a decline in parasitological response in Nigeria [24], decrease in PCR corrected therapeutic e cacy of ACT below 80% in Burkina Faso [25] have been noticed, Moreover, increase in copy number of plasmepsin genes associated with decrease in effectiveness of piperaquine has been arisen in South East Asia [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, AL absorption may have been compromised in this study because it was not administered with fatty food as recommended by the manufacturer [30]; however, drug levels were not collected, making this assertion impossible to ascertain. Evidence of sub-optimal e cacy of AL has been described in some African countries [10,11,31,32]; correct AL administration (i.e., with fatty food) and close monitoring of e cacy for uncomplicated malaria are warranted in Madagascar.…”
Section: Discussionmentioning
confidence: 99%
“…For AL, however, no recent studies to evaluate therapeutic e cacy have been done in Madagascar. Evidence of reduced AL e cacy has been described in SSA [10][11][12]; given that it is the second-line antimalarial in Madagascar, and has at times been used as the rst-line treatment due to shortages of ASAQ, describing its e cacy in Madagascar is important.…”
Section: Introductionmentioning
confidence: 99%